Capability of Paraguaçu estuary (Todos os Santos Bay, Brazil) to form oil–SPM aggregates (OSA) and their ecotoxicological effects on pelagic and benthic organisms. Issue 1 (15th January 2017) - Rios, Mariana C.; Moreira, Ícaro T.A.; Oliveira, Olívia M.C.; Pereira, Taís S.; de Almeida, Marcos; Trindade, Maria Clara L.F.; Menezes, Leonardo; Caldas, Alex. S.
Abstract: For experiments concerning the formation of oil–suspended particulate matter (SPM) aggregates (OSA), oil and sediment samples were collected from Campos Basin and six stations of Paraguaçu estuary, Todos os Santos Bay, Brazil, respectively. The sediments samples were analyzed for organic matter determined by the EMBRAPA method, nitrogen determined by the Kjeldahl method, and phosphorus determined by the method described by Aspila. The oil trapped in OSA was extracted following the method described by Moreira. The experiment showed a relationship between the amount of organic matter and OSA formation and consequently the dispersion of the studied oil. On the basis of the buoyancy of OSA and the ecotoxicological effects on pelagic and benthic community, the priority areas for application of remediation techniques are Cachoeira, Maragogipe, and Salinas da Margarida because of the large amount of oil that accumulated at the bottom of the experiment flask (5.85%, 27.95%, and 38, 98%; 4.2%, 17.66%, and 32.64%; and 11.82%, 8.07%, and 10.91% respectively). Highlights: The sedimentary samples collected have little ability to form OSA. The experiment tends to form OSA with negative buoyancy. Areas with neutral OSA have a good chance to naturally recover. Priority areas to apply remediation method are those where OSA had negative buoyancy.